The Odious Debt Doctrine: The Equitable Rule - Mauro Megliani (German Law Journal)
The odious debt doctrine was envisaged by the Russian jurist Alexander Sack as an exception to the passing rule of a debt in case of state and government succession. An analysis of the practice indicates that this exception was often accompanied by some equitable solution. Although the 1983 Vienna Convention did not acknowledge the doctrine, the equitable distribution of assets and liabilities as a method of settling disputes may allow an application of the doctrine in disguise. This equitable method of settling could come into play if the doctrine found application beyond the strict boundaries of state succession. Such a step would imply the formalization of the doctrine in national legislation, with the result that a loan agreement tainted with odiousness would be illegal and unenforceable. Nevertheless, in common law countries, the laws of which usually govern financial transactions, a claim for recovering what transferred under an illegal contract could be denied based on public policy considerations. This denial of restitution would refrain these countries, traditionally sensitive to creditors’ rights, from acknowledging the doctrine in their legal systems. To overcome this impasse, the formalization of the doctrine should include an equitable approach based on the benefit for the population. This equitable approach would reflect the practice of state and government succession on which the doctrine is usually grounded.